ANALISIS INTERAKSI WILAYAH KOMODITAS PETERNAKAN DI PROVINSI RIAU - Yuhendra Yuhendra; S. Hadi; B. Barus; B. Tjahjono (State Islamic University of Sultan Syarif Kasim Riau, 2011)
The development of livestock potential is expected to reduce of production and market unbalances. The nature ofRiau Province, requires effective and efficient planning in supporting the market of livestock commodities inter-regions.Knowing patterns of marketing of livestock commodities inter-regions able to increase added value of commodities. Thepurposes this research are: 1) to analyze the flow of livestock commodities marketing inter-region in Riau Province, 2) todetermine the direction of livestock commodities development based commodities marketing. This research was conducted inRiau Province with eleven districts and cities. This study used a model analysis of gravity and entropy models with doubleconstrains. The result showed the distance between regions determine interaction inter-region. The flow of cattle marketing isinfluenced by farmers productivity of origin region. Cattle’s production region is directed to Indragiri Hulu, Kampar, RokanHulu and Kuantan Singingi and marketing region to Siak, Bengkalis and Rokan Hilir. The flow of buffalo commoditiesmarketing is more determined by slaughtering in destination region. Buffalo’s production is directed to Kampar and KuantanSingingi and marketing to Pekanbaru, Siak, Dumai and Rokan Hilir. The main factors that determine the flow of broilermarketing is population in origin region and consumption of broiler in destination region. Development of Broiler’sproduction region is directed to Pekanbaru, Kampar, Pelalawan, dan Siak, and marketing region to Bengkalis, Dumai,Indragiri Hilir, and Rokan Hilir. The flow of cattle and buffalo commodities market moves from south to north and Broilermoves from region who were in middle to around it.